Shape feature representation in similarity measurement for content-based image retrieval - Chiew, Kang Leng (Faculty of Computer Science and Information Technology, 2003)
The emergence of digital library and multimedia database require an efficient and effective maintenance technique. A lot of difficulties and limitations arise from the rapid-growing size of these databases. Therefore, content-based image retrieval techniques have been developed to overcome some of the limitations associated with the conventional method.